VAGINAL HYSTERECTOMY PELVIC SURGERY PATIENTS PRIOR: A RESOURCE INTRAOPERATIVE - Siu Au, Alejandro (2015)
Previous surgery in the pelvic area is a relative contraindication for vaginal hysterectomy, the authors describe a process as intraoperative resource contributing to doubts for the implementation of surgery, the surgeon providing security, protecting the physical integrity of the patient. This procedure was performed in fifty patients, vaginal hysterectomy running throughout.